Preservice General Education Teachers’ Attitudes and Knowledge of Special Education - Mahar, Patricia; Terras, Katherine; Chiasson, Kari; Chalmers, Lynne; Lee, Tricia (Journal of the American Academy of Special Education Professionals, 2010)
The purpose of this study was to determine the attitudes and knowledge acquired by preservice general education teachers regarding students with disabilities. Participants included fifty-six general education preservice teaches in their student teaching semester at the University of North Dakota. A three part survey (i.e., attitudes, perceived knowledge, and application of knowledge of special education) was conducted. Participants’ responses indicated that 1) preservice teachers’ attitudes toward inclusion of students with disabilities were highly favorable, 2) preservice teachers’ attitudes were least favorable in the area of managing behavior, 3) preservice teachers’ attitudes were marginal in managing time and overcoming negative attitudes of others, 4) preservice teachers’ perceptions of knowledge in the area of differentiation (e.g., assessment, instruction) were highly favorable, 5) preservice teachers’ perceptions of knowledge in the areas of law, procedures, and severe disabilities was marginal, and 6) preservice teachers’ application of knowledge in the area of characteristics of and accommodations for students with learning disabilities and attention deficit hyperactivity disorder was extremely favorable.